Pharmacophore Based Drug Designing Of Plant Metabolite Axillarin From Inula Britannica Against Native Hiv1 –Protease - DHIVYA.S; SURESH KUMAR.C; VIJAYAKUMAR.B; RETHAVATHI.J; M.KARTHIK ANANTH.; JAYNTHY.C (International Journal of Pharma and Bio Sciences, 2012)
This research focuses on the generation of analogy for axillarin from Inula britannica. Chemical based drugs have tendency to induce more side effects to the human body ,especially the drugs used for treating dreadful disease like HIV shows more side effects to the patients. Thus, the new discoveries of leads are necessary to prevent the patients from side effects. One such a way of achieving is computational drug discovery. The chemical features of axillarin are analyzed by catalyst - Hiphop algorithm and its derivatives are generated based on axillarin Pharmacophore using Minimaybridge. Hence, the lead S00165 shows good absorption, solubility, and high penetrating mode in blood brain barrier with no carcinogenicity and mutagenicity. The analogy S00165 docked with HIV-1 native protease using Ligand-Fit algorithm with Montecarlo simulations and the binding affinity possess -3.89kcal/mol with dock score of 69.785.